Airports for the 80s proceedings of the fourth World Airports Conference, 3-5 April 1973. (Institution of Civil Engineers, 1973)
The conference proceeded with sessions covering transport systems of the future, commercial aircraft, air transport development in the light of changing aircraft technology, world air transport development, passenger and baggage movement, air cargo facilities, and more.